2017
DOI: 10.1155/2017/1390458
|View full text |Cite
|
Sign up to set email alerts
|

Deregulation of Regulatory T Cells in Acute-on-Chronic Liver Failure: A Rat Model

Abstract: Aims. Acute-on-chronic liver failure (ACLF) and acute liver failure (ALF) are similar in many respects during their acute exacerbation; however, ACLF generally has a poorer prognosis. We aimed to investigate the role and dynamic changes of regulatory T cell (Treg) and T helper 17 (Th17) cell proportions during ACLF progress. Methods. All rats were classified into two groups randomly: ACLF group and ALF group (control group). The rat model of ACLF was preestablished by intraperitoneal injection of carbon tetrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
2
26
0
Order By: Relevance
“…WBC count remains a critical marker of prognosis; greater inflammation, as evidenced by a higher WBC count, is associated with worse outcomes. Current data have documented that an excessive immunologic response is part of ACLF initiation . However, the innate and adaptive immune response in the infected versus uninfected patient with ACLF needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WBC count remains a critical marker of prognosis; greater inflammation, as evidenced by a higher WBC count, is associated with worse outcomes. Current data have documented that an excessive immunologic response is part of ACLF initiation . However, the innate and adaptive immune response in the infected versus uninfected patient with ACLF needs further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Current data have documented that an excessive immunologic response is part of ACLF initiation. (26,27) However, the innate and adaptive immune response in the infected versus uninfected patient with ACLF needs further exploration. In addition, understanding the evolution of these responses over time and their role in predisposing patients to second infections requires urgent evaluation to develop intervention strategies that will improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the previously mentioned reports, a Th17/Treg axis imbalance that could have a role in the development of ALF in CHB has been observed. Nevertheless, as well as the studies related to IL-10, the results are diverse; in some studies, it was found a higher frequency of Th17 cells in ACLF, whereas others did not find significant changes in Treg cells [ 136 , 137 , 138 , 139 ].…”
Section: Acute Liver Failure In Hbv Infectionmentioning
confidence: 99%
“…ACLF is an acute deterioration of chronic liver disease characterized by multiple organ failure and high short-term mortality, with 3-month and 1-year mortality rates being 53.7% and 67.4%, respectively (22). ACLF patients are highly susceptible to BIs because these patients display sepsis-like immune paralysis (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%